PROSES RECOVERY DAN PENGKONSENTRASIAN PROTEIN AIR PEREBUSAN PINDANG TONGKOL (Euthynnus affinis) MELALUI ULTRAFILTRASI - Uju, Bambang Riyanto, Bustami Ibrahim, Wahyu Ramadhan, Irfan Setia Tanjung (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
“Pindang” is a fisheries product which is produced by combination of boiling and salting. Boiling in a salt solution causes dissolving protein into the boiling water. Membrane process has been applied for the concentrating of protein. In this study, the characterization and recovery of protein from the boiled water of “pindang” were carried out using 0.05 µm ultrafiltration membrane. The parameters of study included the effect of the concentration factor on the protein concentration, flux of permeate, and protein rejection coefficient. The concentrating of “pindang” boiling water using 0.05 μm ultrafiltration membrane increased 46.75% of protein. During ultrafiltration concentrating process, flux decreased from 6.58 L/m2h at the beginning of the concentration to 2.71 L/m2h at fortieth minute. Rejection coefficient increased from 41.2% at the beginning of the concentrating to 55.07% at fortieth minute. The decreasing values of the parameters COD, TSS, turbidity, protein, and fat were higher than the decreasing of TDS, salinity, and pH. The dominant molecular weight of protein in protein concentrate of “pindang” boiling water was 33.45 kDa.Keywords: protein concentrate, “pindang”, ultrafiltration